De posseiros a proprietários: a reconfiguração agrária no sudoeste do Paraná - 1940-1972 - Rizzarda, Angélica Dalla (2019)
This work has as objective to analyze the question of ownership and land ownership in southwestern Paraná between the years 1940 and 1972; seek to analyze the studies on the role of Cango, Citla, and, finally, the performance of Getsop in the juridical determination of the land. Rather than analyze facts or consequences, what is wanted is to understand the process of action and struggle in the social environment in search of the securitization of the lands of southwestern Parana. The main agent in the land issue in the region in this period was the migrant / squatter. Southwest Paraná has been (re) occupied and (re) organized as a place of opportunity for access to land and reproduction of a way of life based on small rural property, with agricultural activities, family work and surplus production. It has been seen that the history of the region is marked by various struggles throughout its (re) stocking: by delimiting boundaries, to guarantee the right to use, possession and ownership of land. What was outlined in the Southwest was the permanent struggle between the two extreme poles of the land occupation process: on the one side, the land monopoly, on the other, the division of land into small estates. For the agricultural and political elite of the region, the land was conceived as a source of power (political / economic). These different conceptions regarding the role wich was attributed to the land were the origin of the conflicts arisen from the confrontation of interests between the different social groups. After several conflicts and discussions was created, in 1962, by President João Goulart, the Land Executive Group for the Southwest of Paraná (GETSOP), wich had as legal title holder the lands that were causing the conflafration. The results that can be observed throughout the study and which were highlighted, one of them is the importance that GETSOP represented for the Sudoestina population. After armed attacks, the judicial struggle gained an important prominence for the squatters. The group regularized the issue of territorial delimitation, collected data about land and squatters, and finally handed over property titles.